High-Resolution Magic Angle Spinning Proton Magnetic Resonance Spectroscopy in Prostate Cancer - Decelle, Emily A. (2013)
Prostate cancer (PCa) is the most frequently diagnosed malignancy in men worldwide, due in large part to the increased use of the annual serum prostate specific antigen (PSA) screening test for detection. PSA screening has saved lives, but it has also resulted in the overtreatment of many PCa patients because of a limited ability to accurately localize and characterize PCa lesions through imaging. High resolution magic angle spinning (HRMAS) proton magnetic resonance spectroscopy ((1)H MRS) has proven to be a strong potential clinical tool for PCa diagnosis and prognosis. The HRMAS technique allows studies to obtain valuable metabolic information from ex vivo intact tissue samples and also perform histopathology on the same tissue specimens. Studies have found that the quantifications of individual metabolite levels and metabolite ratios, as well as metabolomic profiles, show strong potential to improve accuracy in PCa detection, diagnosis and monitoring. Ex vivo HRMAS has also been a valuable tool for interpreting in vivo results, including the localization of tumors, and thus has the potential to improve in vivo diagnostic tests used in the clinic. Here we primarily review publications of HRMAS (1)H MRS and its use in studying intact human prostate tissue.